Agricultural Markets in Benin and Malawi : The Operation and Performance of Traders - Fafchamps, Marcel; Gabre-Madhin, Eleni (World Bank, Washington, DC, 2014)
Drawing on original surveys of agricultural traders, the authors examine how traders operate in two Sub-Saharan African countries, Benin and Malawi. They find the following: The largest transaction costs for traders are search and transport. Search methods rely principally on personal visits by the trader, which raises search costs. And since enterprises are very small, transport represents a large share of marketing costs. Brand recognition, grading, and quality certification are nonexistent. Brokers and agents are not organized in commodity exchanges. Quantities are not pooled for transport and storage so as to achieve returns to scale. Interseasonal and interregional arbitrage is not feasible for most traders, who prefer to operate day to day in a small territory. This information provides some important insights into how agricultural trade could be improved. It suggests possible policy interventions in four main areas: increasing traders' asset base, reducing transaction risk, promoting more sophisticated business practices, and reducing physical marketing costs.